A laser Raman tweezers study of eryptosis. (11th April 2018) - Barkur, Surekha; Mathur, Deepak; Chidangil, Santhosh
Abstract: Eryptosis—the suicidal death of erythrocytes—is characterized by membrane blebbing and cell shrinkage. Eryptosis can be triggered by various xenobiotics such as carbon monoxide, lead, and amyloid, and by stressors such as oxidative stress, osmotic shock, and rapid alteration of ambient conditions. We have used Raman tweezers spectroscopy to study eryptosis in single, live cells and have attempted to explore the underlying mechanism, specifically to identify possible Raman signatures of eryptosis. Erythrocytes (red blood cells) were exposed to free radicals, silver nanoparticles, glucose, heat, and osmotic shock to induce eryptosis, and a comparison was made of their Raman spectra, which indicated that these conditions lead to a transition of haemoglobin from the R to the T state. Consequences of eryptosis include dehydration, cell shrinkage, and pH changes, which result in deoxygenation of haemoglobin. This, in turn, can be detected by monitoring the wavenumber shifts associated with Raman marker bands of R to T transitions. In addition, the principal component analysis results indicate differentiation among red blood cells undergone eryptosis due to different conditions. Abstract : Raman tweezers spectroscopy of eryptosis was studied by exposing the erythrocytes to stressors such as free radicals, heat, osmotic shock, glucose, and silver nanoparticles. The spectral variations indicate a transition of haemoglobin from R state to T state, which can be used to identify eryptosis and are due to dehydration, cell shrinkage, and pH changes in the cytoplasm. The PCA results shows distinction among erythrocytes undergone eryptosis caused by various stimulants.